Development of a peptide ELISA for the diagnosis of Equine arteritis virus - Metz, German Ernesto (2014)
A peptide-based indirect ELISA was developed to detect antibodies against Equine arteritis virus (EAV). Two peptides for epitope C of protein GP5 and fragment E of protein M were designed, synthesized, purified and used as antigens either alone or combined. Ninety-two serum samples obtained from the 2010 Equine viral arteritis outbreak, analyzed previously by virus neutralization, were evaluated by the ELISA here developed. The best resolution was obtained using peptide GP5. The analysis of the inter- and intraplate variability showed that the assay was robust. The results allow concluding that this peptide-based ELISA is a good alternative to the OIE-prescribed virus neutralization test because it can be standardized between laboratories, can serve as rapid screening, can improve the speed of diagnosis of EAV-negative horses and can be particularly useful for routine surveillance in large populations.